Van de Hulst Essay: The DDA, the RTE, and the computation of scattering by plane parallel layers of particles. (March 2017) - Mackowski, Daniel
Abstract: A formulation and computational algorithm, based on the discrete dipole approximation (DDA), is presented for directly simulating the electromagnetic wave reflection, transmission, and absorption properties of plane parallel layers of random particulate media. The method is intended for situations in which the characteristic size of the particles is comparable to the radiation wavelength, yet no restriction is made regarding the concentration of the particles. In particular, the application is specifically intended for high particle concentrations characteristic of regolith, pigment layers, functional thin films, and so on. Strategies for reducing the memory and time requirements of the computations are developed. Test calculations show that the method can reproduce direct simulation predictions of hemispherical reflectance from layers of spherical particles as calculated by multiple sphere superposition solution. The method also correctly asymptotes to the radiative transport regime in the limit of small particle volume fraction. The connection of the formulation to those for discrete particle scattering, and the radiative transport equation (RTE), is discussed.